PDGF Promotes Dermal Fibroblast Activation via a Novel Mechanism Mediated by Signaling Through MCHR1 - Takamura, Naoko; Renaud, Ludivine; da Silveira, Willian Abraham; Feghali-Bostwick, Carol (Frontiers in Immunology, 2021)
Systemic sclerosis (SSc) is an autoimmune disease characterized by vasculopathy and excessive fibrosis of the skin and internal organs. To this day, no effective treatments to prevent the progression of fibrosis exist, and SSc patients have disabilities and reduced life expectancy. The need to better understand pathways that drive SSc and to find therapeutic targets is urgent. RNA sequencing data from SSc dermal fibroblasts suggested that melanin concentrating hormone receptor 1 (MCHR1), one of the G protein-coupled receptors regulating emotion and energy metabolism, is abnormally deregulated in SSc. Platelet-derived growth factor (PDGF)-BB stimulation upregulated MCHR1 mRNA and protein levels in normal human dermal fibroblasts (NHDF), and MCHR1 silencing prevented the PDGF-BB-induced expression of the pro-fibrotic factors transforming growth factor beta 1 (TGFb1) and connective tissue growth factor (CTGF). PDGF-BB bound MCHR1 in membrane fractions of NHDF and the binding was confirmed using surface plasmon resonance (SPR). MCHR1 inhibitor blocked PDGF-BB modulation of intracellular cyclic adenosine monophosphate (cAMP). MCHR1 silencing in NHDF reduced PDGF-BB signaling. In summary, MCHR1 promoted the fibrotic response in NHDF through modulation of TGFb1 and CTGF production, intracellular cAMP levels, and PDGF-BB-induced signaling pathways, suggesting that MCHR1 plays an important role in mediating the response to PDGF-BB and in the pathogenesis of SSc. Inhibition of MCHR1 should be considered as a novel therapeutic strategy in SSc-associated fibrosis.